Ornamental Fish Cultivation Development through Education and Entrepreneurship to Empower Youth - Setyono, Bagus Dwi Hari; Affandi, Rangga Idris; Fitria, Syawalina; Sumsanto, Muhammad; Asri, Yuliana; Dwiyanti, Septiana; Wahyudi, Rhojim; Nuryadin, Rusmin; Mujib, Abdul Saddam; Alim, Sahrul (Borneo Research and Education Center, 2025)
Freshwater ornamental fish farming has high economic potential, but youth participation in rural areas is still low due to limited access to technical training and entrepreneurial literacy. This community service program aims to empower youth communities in Bagek Nunggal Hamlet, West Lombok, by developing ornamental fish farming based on education and entrepreneurship. The implementation method includes technical training in ornamental fish farming (guppy, platy, molly) with a simple biofilter system, entrepreneurship training, and assistance in establishing community business units. Participatory surveys showed that 76.7% of respondents did not have cultivation skills, and 83.3% had never participated in business training. The results of the activities showed a significant increase in the participants' technical knowledge, entrepreneurial motivation, and digital marketing skills. This program succeeded in encouraging the formation of joint business groups and growing a sustainable local entrepreneurial ecosystem. This intervention proves that an integrative approach between technical training, entrepreneurship, and utilizing local assets can increase young rural communities' capacity and economic independence.